Synthetic pharmacotherapy for lupus nephritis. (22nd January 2017) - Moroni, G.; Ponticelli, C.
ABSTRACT: Introduction : Lupus nephritis is a frequent complication and a major cause of morbidity and mortality in patients with systemic lupus erythematosus (SLE). Area covered : The main characteristics and mechanisms of action of the synthetic drugs more frequently used in lupus nephritis are described. Possible strategies aimed to reduce the potential adverse events without affecting efficacy are reported. Expert opinion : Many synthetic immunosuppressive drugs used in lupus nephritis have a low therapeutic index. Good knowledge of their pharmacologic characteristics, mechanisms of action, and drug-to-drug interactions, coupled with a strategy aimed to increase immunosuppression in the active phases of SLE while reducing the dosage in quiescent periods can reduce the iatrogenic morbidity while maintaining efficacy. Biologic agent may allow to reduce the use or the dosage of synthetic immunosuppressive drugs.